Integrating Diffusion Perspective of Total Quality Management Improvement in SMEs Indonesia Sector: a Bibliometric Analysis - Hartono Subagio (Journal of Entrepreneurship and Business, 2023)
Pupose: Constructing big potential of development by boosting up the SMEs. The SMEs seems neglected by its history as the main focus remained on public sectory. The SMEs particularuy in large scale manufacturing units beyond the government, bank, and liberalization. As the SMEs sector periodly withdraw their development because of lack skill and function. In this research, SMEs sector an object using the improvement of Entreprenurship skill by Human Capital and Social Resources, and Enterpreneurship Education. Method: This research adopts qualitative research method with Bibliometric Analysis. Bibliometric analysis defines the quality of systematic literature with periodical time and quality evidence in empirical studies. Result: Adopting the Systematic Literature and Bibliometric analysis entrepreneurship could responsibility of reality in better recognize and understand the potentional of implementation process. With an evidences by integrating diffusion perspective between Total Quality Management in Indonesia SMEs sector.